2017
DOI: 10.1212/wnl.0000000000004268
|View full text |Cite
|
Sign up to set email alerts
|

MRI-guided focused ultrasound thalamotomy in non-ET tremor syndromes

Abstract: This study provides Class IV evidence that for patients with tremor not caused by essential tremor, MRgFUS of the Vim improves the tremor of the contralateral hemibody at 6 months.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
70
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 83 publications
(87 citation statements)
references
References 13 publications
5
70
0
1
Order By: Relevance
“…MRI‐guided focused ultrasound (MRgFUS) is a novel, incision‐free invasive technique to ablate deep body targets, including brain . Open, single‐blind, and sham‐controlled double‐blind studies have confirmed the safety and efficacy of MRgFUS targeting ventro‐intermedius nucleus (Vim) in PD tremor. Tremor recurrence has been reported in up to a third of patients within the first 2 years, although others have reported a more sustained benefit, similar to that observed after radiofrequency thalamotomy …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…MRI‐guided focused ultrasound (MRgFUS) is a novel, incision‐free invasive technique to ablate deep body targets, including brain . Open, single‐blind, and sham‐controlled double‐blind studies have confirmed the safety and efficacy of MRgFUS targeting ventro‐intermedius nucleus (Vim) in PD tremor. Tremor recurrence has been reported in up to a third of patients within the first 2 years, although others have reported a more sustained benefit, similar to that observed after radiofrequency thalamotomy …”
mentioning
confidence: 99%
“…He participated in our Vim‐MRgFUS for essential tremor (non‐ET) tremor trial (NCT02252380), targeting the dominant hemisphere (Fig. A) . At baseline, total, right‐hemibody and disability tremor rating scale (TRS) scores were 46, 26, and 12 (Supplementary Video Segment 1), respectively, and dropped by 80%, 96%, and 92% 1 week after the first Vim‐MRgFUS procedure (Supplementary Video Segment 2).…”
mentioning
confidence: 99%
“…Fasano and colleagues described a single‐blinded, single‐center, prospective study of 6 patients who underwent unilateral Vim MRgFUS for non‐ET tremor syndromes, 3 of whom were diagnosed with tremor‐dominant PD . All patients were followed to a maximum of 6 months, except for 1 with PD who expired from aspiration pneumonia 4 months postoperatively.…”
Section: Thalamotomymentioning
confidence: 99%
“…Fasano and colleagues described a single-blinded, singlecenter, prospective study of 6 patients who underwent unilateral Vim MRgFUS for non-ET tremor syndromes, 3 of whom were diagnosed with tremor-dominant PD. 36 All patients were followed to a maximum of 6 months, except for 1 with PD who expired from aspiration pneumonia 4 months postoperatively. Six months after the procedure, the remaining 5 patients exhibited a 52.9% decrease in single-blinded assessments of contralateral tremor using the Tremor Rating Scale (Parts A and B).…”
Section: Thalamotomymentioning
confidence: 99%
“…This emerging technology is used primarily for thermal ablation of central brain locations, such as for the treatment of essential tremor and Parkinson's disease. 5,21,41,50 MRg-FUS is an image-guided, noninvasive treatment option that can be used to manipulate the BBB and achieve focal CNS tumor drug delivery of systemically administered treatments. …”
mentioning
confidence: 99%